Play or hard work: Unpacking well-being at preschool. (March 2015) - Kennedy-Behr, A.; Rodger, S.; Mickan, S.
Highlights: Wellbeing/quality of life at preschool is significantly lower for children with developmental coordination disorder (DCD) than typically developing children. Engagement in group play is positively associated with wellbeing for typically developing children providing further support for early childhood policies of play-based curricula. Children with DCD may not experience free-play at preschool as "play" but rather as "hard work". Abstract: Well-being or quality of life is thought to give a more accurate picture of the impact a condition has on day-to-day functioning than traditional outcome measures. This study sought to examine the relationship between engagement in play and well-being for preschool children with and without developmental coordination disorder (DCD). A quasi-experimental design was used with two independent groups of preschool children aged 4–6 years with ( n = 32) and without ( n = 31) probable DCD. Play skills were assessed using the Play Observation Scale based on 30 min of videotape of free-play at preschool. Well-being was assessed using a parent-proxy version of the Revised Children Quality of Life Questionnaire (KINDL R ). Spearman rho correlations were performed to examine the relationship between play and well-being. Well-being at preschool was significantly lower for the children in the DCD group however overall well-being was not significantly different. Engagement in type of social play (solitary, parallel or group) was found to predict well-being for the typically developing children. For the children with DCD, engagement in group play was not associated with well-being. An explanation for this difference may be that children with DCD may not experience free-play at preschool as "play" but rather as hard work. Further research is needed to determine why children with DCD experience lower well-being at preschool than their peers and to investigate children's perceptions of free-play. This may enable teachers and therapists to better support children with DCD in the preschool environment.